Perbanyakan Tanaman Pala (Myristica fragrans Houtt) Dengan Metode Pembiakan Vegetatif - Suratman Sudjud; Hayun Abdullah; Buhari Umasugi; Ramli Hadun; Idris Abd. Rachman (Fakultas Pertanian, Universitas Timor, 2022)
Rootstock affects the success rate of vegetative compatibility through the grafting method. Knowing one of the best rootstock ages that determine the percentage rate of success of the grafting method is the goal of this study. The method used was a randomized block design with 3 treatments for rootstock age 60 days, 90 days, and 120 days. The results showed that the difference in rootstock age affected 90% of the success of vegetative propagation using the connection method on the emergence of new shoots and the number of leaves. The highest percentage of success was in the treatment of rootstock seedlings aged 60 days (48.75%). The highest number of leaves was in the treatment of nutmeg seedling age of 60 days (6 pieces) while the lowest was in the treatment of 120 days (3 pieces).